Gambaran Perilaku Membuang Sampah di Kecamatan Licin Kabupaten Banyuwangi - Risti ana; Ayik Mirayanti Mandagi (Universitas Airlangga, 2022)
Background: As many as 63.3% of 120 people have a bad attitude towards waste management. Poor attitude regarding waste management triggers the behavior of littering which will cause many diseases and pollute the environment. Perceptions and behaviors in littering are evidence that environmental care behavior in the community is still relatively low. Therefore, the purpose of this study is to identify behavioral descriptions that influence people's habits of littering. Objectives: The purpose of the study is to identify a description of behavior that affects people's habits of littering Methods: This research is a descriptive study with a quantitative approach. This research was conducted on all communities in village X. Respondents in the study were 120 people in village X. The data collection method was carried out by in-depth interviews. The research design used was cross sectional Results: : The results show that the level of public education is still relatively low at 65.8%, the next factor is the level of knowledge about waste is classified as good at 43.3%, and the last factor is the attitude of the community regarding waste and waste processing is classified as not good at 63.3%. Conclusions: The cause of the behavior of disposing of waste in the community in Licin District, Banyuwangi Regency is caused by the low level of public education, knowledge and attitudes regarding waste management are also still relatively low and public awareness of the environment is still low